The contribution of the CRP/CD64 axis to renal cancer progression by inducing protumor activation of tumor‐associated macrophages - Cheng Pan; Yukio Fujiwara; Hiromu Yano; Toshiki Anami; Yuki Ibe; Lianbo Li; Yuji Miura; Takanobu Motoshima; Shigeyuki Esumi; Junji Yatsuda; Taizo Hibi; Tomomi Kamba; et al. (Clinical & Translational Immunology)
Abstract Objectives C‐reactive protein (CRP) is a well‐known acute‐phase protein that increases remarkably under various inflammatory conditions and is elevated in patients with malignant tumors. In this study, we investigated the influence of CRP on the tumor microenvironment in clear cell renal cell carcinoma (ccRCC). Methods This study explored CRP's role in ccRCC by co‐culturing human macrophages with ccRCC cells and employing antibody blocking, RNA sequencing and in vitro experiments for functional insights. We also analysed The Cancer Genome Atlas Program (TCGA) data to link CD64 expression with ccRCC prognosis and used immunohistochemistry to associate CD64+ macrophages with tumor severity and systemic CRP levels. Results A co‐culture study using human macrophages and RCC cell lines showed that CRP‐stimulated macrophages secrete IL‐6, which induces RCC proliferation via STAT3 activation. CRP‐induced protumor activation of macrophages was suppressed by CD64 blocking antibodies. Furthermore, CRP elevates PD‐L1 expression in macrophages via the CD64‐STAT1 signalling pathway. Statistical analysis of TCGA data indicated that increased CD64 expression was associated with a worse clinical course in ccRCC. Immunohistochemical analysis of pathological specimens revealed that high CD64 expression in tumor‐associated macrophages (TAMs), and a high density of CD64+ TAMs, was linked to high nuclear grade and stage. High CD64 expression was also correlated with increased serum CRP levels. Conclusions The CRP‐CD64 signal was linked to the protumor activation of TAMs and could be a promising target for anticancer immunotherapy in ccRCC.